Self-incompatibility characterization in segregating populations of apple trees with dna markers for s-alleles Caracterização da autoincompatibilidade em populações segregantes de macieira via marcadores de dna para alelos s - Brancher T.L. (2021)
© 2021, Sociedade Brasileira de Fruticultura. All rights reserved.The objective of this study was to characterize the parents and respective populations of apple trees regarding S-alleles to confirm their genealogy and to evaluate the efficiency of the molecular markers used. Sixteen specific sets of primers were used for identification of apple S-alleles by PCR. Two segregating populations of the Epagri Apple Breeding Program resulting from crosses between ‘Fred Hough’ × ‘Monalisa’ and ‘M-11/00’ × ‘M-13/91’ were evaluated. The expected segregations are 1:1:1:1 for full compatibility and 1:1 for semi-compatibility, which can be confirmed by the X2 test. The ‘Fred Hough’ (S5 S19 ) × ‘Monalisa’ (S2 S10 ) cross proved to be fully compatible; and two triploids were identified among the hybrids as well. The ‘M-11/00’ (S3 S19 ) × ‘M-13/91’ (S3 S5 ) cross was characterized as semi-compatible based on DNA markers, and the segregation of the S-alleles in the hybrids was 1:1, as expected. The segregation of the DNA markers occurred together with their respective S-alleles: S2, S3, S5, S10, and S19 . Thus, characterization of the S-alleles not only allowed identification of compatibility between parents but also identified contaminations in segregating populations.